Improvement of the In Vitro Culture of Echinococcus Granulosus Metacestodes - Elissondo, María Celina (2017)
This work introduces a novel modification to the in vitro experimental vesiculardevelopment of the parasite. Our findings showed that protoscoleces exposed toinsulin developed into microcysts in shorter times. Moreover, a tenfold incrementin the yield of microcysts per tube was observed. An improvement of the in vitroculture of E. granulosus metacestodes was achieved. On the basis of this axenicin vitro system, biochemical, molecular and chemotherapeutical studies of E.granulosus will be greatly facilitated.